A comparative study on the performance of RESET based electro-thermal process in ring shaped confined Ge2Sb2Te5 and Ge1Cu2Te3 chalcogenide memory structures. (December 2017) - Ghosh, Atanu; Sinha, Jayee; Chattopadhyay, Sanatan
Highlights: Comparative performance of RCC cell structure with other PCRAM structures. Performance analysis of Ge2 Sb2 Te5 and Ge1 Cu2 Te3 phase change memory material. Power consumption of Ge1 Cu2 Te3 is 1.62 mW and Ge2 Sb2 Te5 cell is 2.83 mW. Power reduction of 42.75% in Ge1 Cu2 Te3 cell is observed along with lower thermal stress when compared to Ge2 Sb2 Te5 . Phase change occurs at 1.75 V for Ge1 Cu2 Te3 and 2.55 V for Ge2 Sb2 Te5 cells. Abstract: This work presents the comparative performance analysis of Ge2 Sb2 Te5 (GST) and Ge1 Cu2 Te3 (GCT) based phase change memory materials with ring-shaped confined chalcogenide (RCC) cell structure. Three-dimensional finite element simulation with rotational symmetry is used to analyze the electro-thermal process within the RCC cell during phase change operation. The RCC cell structures show superior performance in terms of power consumption required for phase change as compared to other reported PCRAM structures. The results indicate that during the transition from low to high resistance, GCT cell shows superior performance compared to GST cell with power consumption of 1.62 mW and 2.83 mW, respectively. Also, 42.75% reduction in power consumption has been observed in the proposed GCT cell. The GCT based RCC cell requires a relatively lower voltage of 1.75 V for phase transition in comparison to 2.55 V in a GST RCC cell of similar dimension.